Penerapan Metode Geolistrik Resistivitas Konfigurasi Wenner Untuk Mengetahui Dugaan Rembesan Polutan Sampah Di Sekitar Tempat Pembuangan Akhir (TPA) Desa Tanjung Belit Kabupaten Rokan Hulu - Ika Daruwati; Meilan Demulawa (Jurnal Riset Fisika Indonesia, 2020)
A resistivity geoelectric research has been carried out to identify the suspected seepage of garbage pollutants around the Tanjung Belit village garbage dump. The study was conducted in 2 tracks. On track 1 with a track length of 100 m and 35 measurement points, the resistivity is in the range of 0.795-50.1 Ωm. On the 2nd track, 75 m long and 32 measuring points. The method used is the geoelectric resistivity method of the Wenner configuration with data processing using the res2dinv application which has a large resistivity ranging from 1.22-44.9 Ωm. Based on this resistivity, it can be seen that there is waste pollutant seepage located at a depth of 0.825–7.41 m. Keywords:Wenner, geolistric method, RES2DINV